ОБРАЗОВАНИЕ ДИПЛОМАТИЧЕСКИХ ТЕРМИНОВ МОРФОЛОГИЧЕСКИМ СПОСОБОМ (в азербайджанском и французском языках) - Акчурина, И. (Eurasian Journal of Philology Science and Education, 2015)
The process of diplomatic terms formation is realized by means of suffixes and prefixes in French, whereas in Azerbaijani language by means of affixes and loan worded prefixes. Comparative study of Azerbaijan and French languages has indicated that in Azerbaijani language formation of diplomatic terminology by means of prefixes is not characteristic. Therefore, the given language uses either loan words, or the international terminology.